2013 IEEE Power &Amp; Energy Society General Meeting 2013
DOI: 10.1109/pesmg.2013.6672448
|View full text |Cite
|
Sign up to set email alerts
|

Performance prediction of a vanadium redox battery for use in portable, scalable microgrids

Abstract: Vanadium redox batteries (VRBs) have proven to be a viable energy storage technology for portable microgrids due to their rechargeability and high energy density. Pumping electrolyte across the membrane during charging and discharging cycles of the VRB leads to a parasitic load loss. To ensure the electrical equipment is not exposed to extreme ambient temperatures, VRBs must also have temperature control in the form of heating, ventilation and air conditioning, which also result in parasitic load loss. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The paper explains that because the energy source of inverter-based microgrids responds slowly, ESS is only necessary for inverter-based microgrids with a mostly critical load designed to have a power quality higher than the utility grid, and is optional for other types of microgrids. The study in [29] focuses on empirically characterizing Vanadium Redox batteries efficiency, as a viable ESS technology for portable microgrids, based on known climatic operating conditions and load requirements. The study in [30] proves that ESSs applied in microgrids can perform the task of active power balancing and voltage regulation at the same time.…”
Section: Distributed Energy Resource Technologies For Microgridsmentioning
confidence: 99%
“…The paper explains that because the energy source of inverter-based microgrids responds slowly, ESS is only necessary for inverter-based microgrids with a mostly critical load designed to have a power quality higher than the utility grid, and is optional for other types of microgrids. The study in [29] focuses on empirically characterizing Vanadium Redox batteries efficiency, as a viable ESS technology for portable microgrids, based on known climatic operating conditions and load requirements. The study in [30] proves that ESSs applied in microgrids can perform the task of active power balancing and voltage regulation at the same time.…”
Section: Distributed Energy Resource Technologies For Microgridsmentioning
confidence: 99%
“…The pump speed is associated with the VRB SOC and in the deployed system, it is a five stage gear pump [19]. Gear staging is a function of both SOC and VRB output power and is consistent during both charge and discharge periods.…”
Section: Fig 6: Pump Control Loopmentioning
confidence: 99%
“…Those environmental factors may also impact the operational efficiency of the energy storage devices. For example, Vanadium Redox Batteries (VRBs) and other batteries are impacted by ambient temperature [6].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [8] found that the performance of a PV system is mainly influenced by weather, solar irradiance, and module temperature and were able to develop an evolutionary programming algorithm to predict the performance of a grid-connected PV system based on those influences. Guggenberger et al [6] created a microgrid performance model which characterized the performance of a PV/VRB microgrid based on the operation of a backup diesel generator. This deterministic model used typical meteorological year 3 (TMY3) data for the Global Horizontal Irradiance (GHI) and temperature input values for a microgrid located at Fort Leonard Wood in Pulaski County, Missouri.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation